Die moderne Architektur in Island in der ersten Hälfte des 20. Jahrhunderts. Transferprozesse zwischen Adaption und Eigenständigkeit - Seelow, Atli Magnus (2011)
»Modern architecture in Iceland in the first half of the 20th century« explores how modern architecture ends up in a peripheral country and is transformed through its adaptation to the local context — what currents and ideas are absorbed by the first generation of Icelandic architects abroad and adjusted to the native environment, taking Iceland as an example. This transfer offers a unique possibility of observing the spread of modern architecture ›en miniature‹. Because of the comparatively small numbers of architects, the processes of transfer and adaptation can be seen as a whole. In addition, in no other country in europe is the modernisation of architecture so directly influenced by the rapid social changes and technical innovations that have catapulted the country from the middle ages to modern times within a few decades. The book provides a comprehensive overview of Icelandic architecture in the first half of the 20th century and is based on the evaluation of untapped source material.